2023
DOI: 10.1109/tgrs.2023.3334867
|View full text |Cite
|
Sign up to set email alerts
|

Ice-Core Micro-CT Image Segmentation With Deep Learning and Gaussian Mixture Model

Faramarz Bagherzadeh,
Johannes Freitag,
Udo Frese
et al.

Abstract: Ice cores of polar regions (ice sheets) are one of the most prominent natural archives that can reveal essential historical information from the past environment of our planet. The ice core microstructure is a key feature in determining the principal properties of ice such as pore close-off, albedo, and melt events. Micro-CT scans can provide valuable information about the microstructure of materials, although achieving a highquality automated segmentation of porous materials, especially with phase/density cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Numerous investigation studies were presented in the literature linked to deep learning depend ICMCTS, some current works are reviewed here, Bagherzadeh, et al [22] have suggested ICMCTS with DL and GMM. Here, presents new method to enhance segmentation of porous microstructures: DL method (U-net) was trained on higher-resolution (30 µm) data using weak segmentation [GMM] as ground truth, in order to segment low-resolution (60 µm) data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous investigation studies were presented in the literature linked to deep learning depend ICMCTS, some current works are reviewed here, Bagherzadeh, et al [22] have suggested ICMCTS with DL and GMM. Here, presents new method to enhance segmentation of porous microstructures: DL method (U-net) was trained on higher-resolution (30 µm) data using weak segmentation [GMM] as ground truth, in order to segment low-resolution (60 µm) data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is one indicator of ML method's performance the quality ofpositive prediction made by method. It refers to number of true positives divided by total positive predictions as given in equation (22).…”
Section: ) Precisionmentioning
confidence: 99%